Analisis Harga Pokok Produksi Untuk Penentuan Harga Jual Es Balok di Pabrik Es Ma’un Baarid Sukorejo Situbondo - Luckman Ashary; Abd. Hafidh Ali; Alif Akbarul Muslim (Mazinda : Jurnal Akuntansi, Keuangan, dan Bisnis, 2023)
The cost of production is a crucial aspect in industrial companies. The cost of production will affect the planning of the production cost budget and the selling price of the product. Inaccuracy in calculating the cost of production will result in a selling price that is less competitive or does not match the production costs incurred by the company. So that every company must calculate and apply the right method, in order to produce the cost of production and selling prices accordingly.This research is a type of qualitative research, which was carried out in the office of the Ma'un Baarid block ice factory belonging to the Sukorejo Islamic Boarding School, Situbondo. Data were collected from primary and secondary sources through observation, interviews and document analysis. Data from the field were tested for validity using the triangulation method and discussions with colleagues.The conclusions generated in this study, that there is a large enough difference between the cost of production applied by companies with the variable costing and full costing methods. This difference is more due to factory overhead costs that are not included in the process of calculating the cost of production.